Mechanical Properties and Microstructural Evaluation of Dissimilar Friction Stir Weld of AA6061 Aluminium Alloy and AA5083 Aluminium Alloy - ., Muhamad Fadhli Bin Rosli (IRC, 2016)
such as automobile, aerospace and also on plastic production. However, this welding process still contain defects on the product if it is not conduct properly, especially dissimilar FSW. Dissimilar FSW is considered a challenging method due to variation of chemical and mechanical properties of the base materials. The challenges are to joint two different materials which could cause chemical reaction during welding process and increase the strength and mechanical properties of the welded joint. This project focuses on Dissimilar FSW of AA6061 and AA5083 alloy in order to analyze its mechanical properties and microstructural evaluation of the welded materials. Out of 6 factors that could affect the welded joint, this project focuses on one factor, that is the travel speed of FSW machine. With varying travel speed, the result is determined by performing Vicker Hardness test and Optical Microscopy test on welded joint to determine the mechanical properties and microstructural evaluation. From this test, our project has concluded that when travel speed increase, the hardness value on welded joint will decrease, and microstructure of welded joint also changed